A Measurement for Social Experience and Its Evaluation: A Case Study of University Student - Felix, Felix; Regina, Sharlene; Ohyver, Margaretha; Gunawan, Alexander Agung Santoso; Ngarianto, Heri (Bina Nusantara University, 2025)
Social experience refers to interactions and relationships that individuals have with others within their environments. According to researchers, higher levels of social experience can affect many aspects that an individual has, such as self-awareness, social skills, moral reasoning, intelligence, and emotional intelligence. Despite its importance, it is difficult to determine the valid and reliable measurement of social experience. The writer decided to create a survey as a measurement of social experience with 2 latent variables: self-efficacy and self-regulation to know the influence of both indicators on the measurement of social experience with 300 Bina Nusantara University students as its respondents. From the results of the survey, we conclude that verbal persuasion is the most impactful source from self-efficacy that influences social experience, while motivation is the most impactful source from self-regulation that influences social experience. All self-efficacy and self-regulation statements both are valid and reliable with convincing results. Although our results are convincing, it is essential to bear in mind that this study is not without limitations. These limitations include a limited sample size and the potential for biases in sampling and response due to the characteristics of our participants. Therefore, it is advisable for future research endeavors within this field to select participants from various universities and implement preliminary testing procedures to authenticate the survey.